2015
DOI: 10.1007/s40037-015-0197-5
|View full text |Cite
|
Sign up to set email alerts
|

Fostering informed empathy through patient-centred education about persons with disabilities

Abstract: IntroductionHaving a disability can negatively affect provider-patient communication. Persons with disabilities report the need for better communication with their health care providers and argue that education regarding disabilities is lacking for health care professionals. We sought to determine if a patient-centred curriculum focused on individuals with disabilities could foster the development of informed empathy.MethodsAn educational module to enhance health care students’ capacity for informed empathy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…In the meantime, discussion of necessary tradeoffs in navigating the system becomes particularly relevant in light of the expanding role of patient navigators through the Patient Protection and Affordable Care Act (signed into law in 2011) 30,37 and the interventions focused on improving the provider-patient relationship. 21,31,32 With this focus in mind, our research team applied the current domain analysis to guide the development of a peer-led phone intervention currently being tested, to empower consumers with chronic SCI in getting their primary health care needs met.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, discussion of necessary tradeoffs in navigating the system becomes particularly relevant in light of the expanding role of patient navigators through the Patient Protection and Affordable Care Act (signed into law in 2011) 30,37 and the interventions focused on improving the provider-patient relationship. 21,31,32 With this focus in mind, our research team applied the current domain analysis to guide the development of a peer-led phone intervention currently being tested, to empower consumers with chronic SCI in getting their primary health care needs met.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps a PCP's caring and collaborative demeanor fosters or indicates the presence of other desirable qualities. Provider training that targets caring and collaborative qualities would seem feasible in light of intervention research that demonstrates the efficacy of provider training programs to improve patients' perceptions of provider empathy 31,32 and perceptions of providers' rehabilitation-specific communication skills. 21 Presumably, trade-offs in PCP choice occur out of necessity due to the lack of providers with SCI expertise 14,29 and/or the lack of data to help locate knowledgeable PCPs.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there are many research studies suggesting that the focus on the work with people with disabilities during the study process can be linked to a better situation of people with disabilities in the health system. For example, the inclusion of health-focused subjects in the studies of health workers has been found to have a positive effect on student attitudes, making it easier for them to interact with people with disabilities (Tracy & Iacono, 2008;Miller, 2015;Sarmiento et al, 2016;Ioerger et al, 2019;Kirshblum et al, 2020). It is also revealed that there is a direct link between the knowledge and negative attitudes towards people with disabilities expressed by the health professionals, and that negative health worker attitudes also have a negative effect on the quality and accessibility of health services for people with disabilities (Sabharwal, 2001;Symons, McGuigan, Akl, 2009;Hearn & Hearn, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Without such education, clinicians may hold unconscious negative bias regarding people with disabilities. 22 Clinicians may also lack knowledge about the interaction between specific disabilities and conditions such as pregnancy. 12,23 Specific to reproductive health and maternity care, several qualitative studies report that women with physical disabilities often perceive their clinicians as possessing negative attitudes regarding sexuality, motherhood, and childbearing among people with disabilities.…”
Section: Introductionmentioning
confidence: 99%